2021
DOI: 10.3390/ani11092678
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of, and Attitudes towards, Live Fish Transport among Aquaculture Industry Stakeholders in China: A Qualitative Study

Abstract: China is the largest food fish producer in the world. Chinese consumers normally purchase fish that are still alive to ensure freshness. Therefore, the live transport of fish is important in China’s aquaculture, although it carries potential risks for animal welfare. This study investigated the attitudes and knowledge of stakeholders within Chinese aquaculture towards the live transport and welfare of fish. Semi-structured interviews were conducted with 12 participants who were involved with the aquaculture in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 67 publications
3
14
2
Order By: Relevance
“…By and large, demo farm products were expected to be more expensive than from participants’ farms; however, higher education of any kind lowered support for this assertion. This somewhat contradicts other findings from China showing educational levels generally correlate positively with income (Su and Heshmati, 2013), and people with a higher income have been found to be less sensitive to pricing (Choi, 2016; Wakefield and Inman, 2003) and more concerned about animal welfare (You et al, 2014). Despite the perceived product expense, this did not translate into perceived product quality, with less than half of participants believing the product quality would be better than their own farms.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…By and large, demo farm products were expected to be more expensive than from participants’ farms; however, higher education of any kind lowered support for this assertion. This somewhat contradicts other findings from China showing educational levels generally correlate positively with income (Su and Heshmati, 2013), and people with a higher income have been found to be less sensitive to pricing (Choi, 2016; Wakefield and Inman, 2003) and more concerned about animal welfare (You et al, 2014). Despite the perceived product expense, this did not translate into perceived product quality, with less than half of participants believing the product quality would be better than their own farms.…”
Section: Discussioncontrasting
confidence: 82%
“…This may be a reflection of confidence/knowledge of their own products or they may be less convinced that farming approaches and animal welfare standards impact product quality, although previous surveys in China have suggested strong perceived links in the general public between animal welfare and product quality/safety (Carnovale et al, 2022; Liang et al, 2022). Participants with higher education may have more knowledge about the relationship between animal welfare and product quality (You et al, 2014); however, in this study, university graduates were not significantly different from school-educated participants and only participants with technical college backgrounds rated product quality more highly.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Yang et al ( 46 ) found that Chinese fish stakeholders were also familiar with the term ‘animal welfare,' although some felt that this concept referred more to terrestrial animals, and dissimilarities between fish and humans made fish welfare less of a concern [see also Miralles et al ( 47 )]. In contrast, workers in this study described a variety of factors important to cattle, including physical and mental health, natural living, environmental conditions, and the caregivers involved.…”
Section: Discussionmentioning
confidence: 99%